Community Participation Model in Village Fund Management in Tanjungsari Village, Pacitan District, Pacitan District - Aida Fatma; Lego Karjoko (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Villages play an important role in realizing development and community welfare, which is supported by the issuance of new statutory policies, namely Law Number 6 of 2014 concerning Villages. This law aims to accelerate rural development, improve the welfare of village communities and equalize development in Indonesia. Apart from that, this law is also the basis for granting the broadest possible authority to village or village governments to regulate their own areas as autonomous villages. To achieve this goal, the government since 2015 has disbursed village fund budgets to every village throughout Indonesia. This research uses normative legal research methods, using a statutory approach. This research reveals that community participation in Tanjungsari Village in every village fund management shows optimal participation. At the planning stage, community participation can be seen during the musdus and musdes determining village expenditure priorities, at the implementation stage, community participation takes the form of property participation and mutual cooperation participation and participating in various training programs properly, and at the accountability stage, the community participates during the LPJ APBDes deliberations. Community participation in managing village funds in Tanjungsari Village is at the fifth level of participation, namely placement according to Arnstein's theory or the degree of Tokenism.